Railway track location estimation using onboard inertial sensors. Issue 10 (3rd October 2022) - Peinado Gonzalo, Alfredo; Entezami, Mani; Roberts, Clive; Weston, Paul; Stewart, Edward; Hayward, Mick; Hsu, Sin Sin
Abstract : In railways, using a track- and ride-quality monitoring system on in-service train has become desirable for coordination and security. Identification of the track- or train-related rough rides via train crew can be estimated to the nearest kilometre. However, if the train is equipped with a monitoring system a better location and track quality evaluation can be provided. These systems commonly use information such as GNSS and/or an odometer to provide location information. This work proposes a practical method for track alignment estimation using real data from an in-cab inertial measurement system and using also a novel method based on crosslevel variations. The speed estimation is done through speed-related harmonics detected on inertial sensors, which depend on speed and track characteristics; and distance correction is provided by comparing crosslevel derived from inertial sensors and a reference track geometry. The effectiveness and accuracy of the method is demonstrated with data collected between London and Ashford.